Perbedaan Nilai Laju Endap Darah (Led) dengan Metode Westergreen Manual dan Automatic Convergys Esr 10s di Puskesmas Pasar Minggu - Aulia Mutiara Hikmah; Wicka Maria Tarigan (Yayasan Literasi Sains Indonesia, 2022)
Examination of the erythrocyte sedimentation rate (LED) can be done by manual or automatic Westergreen methods. LED automatic machine used at the Pasar Minggu Subdistrict Health Center is the Convergys ESR 10s. This study aims to determine the difference in the measurement of the erythrocyte sedimentation rate using the Manual Westergreen for 1 hour and Automatic 30 minutes at the Pasar Minggu Subdistrict Health Center. The study used a comparative descriptive method, namely by comparing the results of the comparison of Westergreen's manual erythrocyte sedimentation rate (ED) measurement with the ICSHS standard and the Automatic method using the Convergent tool using statistical test data analysis of the Paired sample T-test. The results of the LED examination samples were analyzed by Kolmogorov-Smirnov to determine the results of the P-value of 0.20 (P-value > 0.05) the data was normally distributed so that the data could be tested using the Paired Sample T-Test. The results with the paired sample T-Test test obtained a P-value of 0.877 (P-value > 0.05). This result can be interpreted that H0 is accepted and H1 is rejected, that there is no significant difference between Westergreen's manual erythrocyte sedimentation rate and the Automatic method.